A remarkable case of intrauterine intussusception, ileal atresia, and complicated meconium ileus: A case report - Hencke, Jonathan; Diez, Oliver; Loff, Steffan (Journal of Neonatal Surgery, 2024)
Background: Intrauterine intussusception, although very rare (<2%), is a potential cause of intestinal atresia. It usually manifests as bowel obstruction during the first hours or days of life. Case Presentation: We report a case with fetal ascites prompting early Cesarean section, with subsequent percutaneous abdominal drainage and laparotomy. Intraoperative findings showed meconium peritonitis and type IIIa ileal atresia with intussusception of the distal part, with the necrosed intussusceptum likely causing perforation and ileal atresia; in addition, the distal ileum demonstrated signs of meconium ileus. After ileostomy creation, the postoperative course was uneventful. Cystic fibrosis was excluded via a sweat test. Conclusion: Prompt diagnosis and management of neonatal intestinal obstruction secondary to the unusual combination of fetal ascites, intussusception, complicated meconium ileus, and ileal atresia results in a favorable outcome.